Development, verification, and implementation of an eDNA detection assay for emydids with a case study on diamondback terrapins, Malaclemys terrapin, and red eared slider, Trachemys script elegans - Andrew T. Fields; Elizabeth P. Hunt; Katherine Lanoue; Aaron S. Baxter; Riley S. Sebby; W. Jay Tarkington; David S. Portnoy (Conservation Genetics Resources, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 2. An Evaluation of the Predictive Ability of Effects-Based Sediment-Quality Guidelines - Donald D. MacDonald; Christopher G. Ingersoll; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Ning Wang; Corrine Severn; Ron Gouguet; John Meyer; Jay Field (Archives of Environmental Contamination and Toxicology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Facile reduction of arsenate in methanogenic sludge - Jim A. Field; Reyes Sierra-Alvarez; Irail Cortinas; Gumersindo Feijoo; Maria Teresa Moreira; Mike Kopplin; A. Jay Gandolfi (Biodegradation, 2004)